Developing Joyful Story Sheets (JoSS): an Effort to Build Character for EYL Learners in Indonesia through Reading JoSS - Iftanti, Erna; Madayani, Nany Soengkono (Dinamika Ilmu: Jurnal Pendidikan, 2019)
In response to character education stated in Indonesian Curriculum 2013, to build characters for students of early ages is significant. This can be built through establishing reading habits and building character education to young learners living in urban and suburban areas simultaneously. However, there is lack attention paid to those living in suburban areas. Thus, this research is intended to provide them with some appropriate character-based reading materials. In order that they enjoy reading, the reading materials should be joyful and arouse imagining. This research employs Research and Development (Borg and Gall, 1983 & Ari, et.al., 1985) with the data were collected through doing need analysis by means of distributing questionnaire to EYL in suburban areas in East Java Indonesia, interviewing EYL teachers and parents having children at elementary schools. The results of the data collecetd in Need Analysis were used to develop the product. This R and D produced collection of Joyful Story Sheets (JoSS) for EYL of the 3rd, the 4th, the 5th, and the 6th graders with each grade consists of 40 joyful story sheets written based on some characters, i.e. hard working, independence, discipline, honesty, and tolerance. The research reveals that the product of this research-namely JoSS- is proved to inspire the students’ moral values, to build love of reading, and to encourage learning English. This research result is pedagogically implemented not only as a means of character education but as supplementary materials for reading class as well. To prove its effectiveness, it is suggested for further researchers to experimentally investigate.